Spatial Temporal Expansion of Harmful Algal Blooms in Chile: A Review of 65 Years Records - Camila Barría; Piera Vásquez-Calderón; Catalina Lizama; Pablo Herrera; Anahi Canto; Pablo Conejeros; Orietta Beltrami; Benjamín A. Suárez-Isla; Daniel Carrasco; Ignacio Rubilar; Leonardo Guzmán; L. René Durán; et al. (Journal of Marine Science and Engineering, 2022)
Harmful Algal Blooms (HABs) have been classified depending on the causative organism and its impacts: non-toxic HAB (microalgae capable of affecting tourism and causing oxygen deficiency, which generates mortality of marine organisms), toxic HAB (microalgae capable of transferring toxins to the food chain), and ichthyotoxic HAB (microalgae capable of generating mechanical damage in fish). HABs represent a worldwide problem and have apparently increased in frequency, intensity, and geographic distribution at different latitudes. This review details the occurrence of HAB events in the Southeast Pacific, Chile, over a 65-year period, analysing two of the three types of HAB described: toxic and ichthyotoxic HABs. For this, we conducted a review from many different scientific sources and from the written press and social media, that have mentioned HAB events in the country. In Chile, the microalgae involved in HAB events are dinoflagellate (52%), diatoms (33%) and silicoflagellate (10%), with a total of 41 species and/or genera described in the literature. A total of 501 HAB events were recorded in Chile between 1956 and 2021, where 240 (47.9%), 238 (47.5%), 14 (2.7%), 8 (1.5%) and 1 (0.2%) event were caused by diatoms, dinoflagellate, silicoflagellate, raphidophycean and haptophyte, respectively. An apparent increase in the frequency of HAB events is observed since the first record in 1956, with a maximum of 46 events during the years 2017 and 2019. The highest incidence in fish is caused by the group of silicoflagellate, raphidophycean and haptophyte (23 events), where 10 events caused mortalities in salmon with an incidence rate of 43.4%. Unlike what is observed with diatoms and dinoflagellate, the events associated with these groups are less frequent, but hold a much higher salmon mortality rate. During the last 65 years, HAB’s geographic extent shows an apparent trend to increase south-to-north. However, the identification of events is closely linked to the areas where much of the country’s aquaculture is located and, therefore, it could be biased. In turn, it is observed that the apparent increase in HAB events could be associated with a greater monitoring effort after major events (e.g., after the 2016 HAB event). On the other hand, it is also recognized a lack of knowledge about harmful algae throughout the Chilean Humboldt Current system, particularly in the northern regions, such as Atacama and Coquimbo. Therefore, the total number of blooms that have occurred in fjords and channels, particularly those that have caused minor economic impacts for artisanal fishermen and the salmon and mussel farming sector, might be underestimated.